DOI: 10.25148/etd.fi08081501
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Quorum Sensing Agents from South Florida Medicinal Plants and their Attenuation of Pseudomonas Aeruginosa Pathogenicity

Abstract: This dissertation, written by Allison L. Adonizio, and entitled Anti-quorum sensing agents from south Florida medicinal plants and their attenuation of Pseudomonas aeruginosa pathogenicity, having been approved in respect to style and intellectual content, is referred to you for judgment.We have read this dissertation and recommend that it be approved. Each plant presented a distinct profile of effect on QS genes and signaling molecules, suggesting varying modes of action. Virulence attenuation was observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 165 publications
(290 reference statements)
2
22
0
2
Order By: Relevance
“…As previously mentioned, E. sibthorpina essential oil did not show potential in the reduction of biofilm synthesis, while F. macedonica oil expressed low activity. In our work, the anti-QS effects of tested extracts varied against different virulent factors, which is in agreement with the study of Adonizio (2008) where various plant extracts had different activity on P. aeruginosa. This bacterium uses the ability to form a biofilm controlled by gene expression, as a resistance to the antibiotics and as a protection from the host's immune system.…”
Section: Anti-qs Activity Of Extracts and Essential Oilssupporting
confidence: 78%
See 2 more Smart Citations
“…As previously mentioned, E. sibthorpina essential oil did not show potential in the reduction of biofilm synthesis, while F. macedonica oil expressed low activity. In our work, the anti-QS effects of tested extracts varied against different virulent factors, which is in agreement with the study of Adonizio (2008) where various plant extracts had different activity on P. aeruginosa. This bacterium uses the ability to form a biofilm controlled by gene expression, as a resistance to the antibiotics and as a protection from the host's immune system.…”
Section: Anti-qs Activity Of Extracts and Essential Oilssupporting
confidence: 78%
“…On the other hand, essential oils of Apium graveolens, Foeniculum vulgare, Petroselinum crispum and Trachyspermum ammi (Apiaceae) did not show anti-QS potential on C. violaceum CV12472 and CVO26 strains (Khan et al, 2009). Obtained differences in the activity of the samples recorded for anti-biofilm and anti-pyocyanin tests may originate from to the complex chemical composition of the extracts and essential oils and the possible synergism of various components (Adonizio, 2008). According to presented data in this work, ethanol extracts of E. sibthorpiana roots had moderate anti-QS activity and similar results were observed by Nagy (2010) for Eryngium aquaticum and Foeniculum vulgare root ethanol extracts.…”
Section: Anti-qs Activity Of Extracts and Essential Oilssupporting
confidence: 76%
See 1 more Smart Citation
“…In a study by Adonizio22, among the plants tested, Conocarpus erectus and Bucida bucerus showed maximum inhibitory activity against QS in P. aeruginosa and were further tested for supression of virulence. Both plants showed significant decrease in LasA activity.…”
Section: Discussionmentioning
confidence: 99%
“…Developing new, non-toxic, and broad-spectrum anti-quorum sensing drugs from both microorganisms and plants is of great interest in recent years. Plants produce diverse antimicrobial compounds such as simple phenolics, catechins, quinones, flavanones, polyphenolics, alkaloids, and terpenoids [2, 20, 21]. Hence, bioscreening plant extracts for antiquorum sensing activity, followed by isolating the compounds responsible for this activity, is rational [22].…”
Section: Introductionmentioning
confidence: 99%